Evaluation of cold atmospheric-pressure plasma against burn wound infections and gene silencing - Ensieh Abbasi; Jalil Fallah Mehrabadi; Mohamadreza Nourani; Yasaman Nazar Namini; Siamak Mohammadi; Davoud Esmaeili; Asieh Abbasi (Iranian Journal of Microbiology, 2021)
Background and Objectives: Non-thermal atmospheric-pressure plasma or cold plasma is defined as an ionized gas. This study aimed to investigate the effect of cold plasma on Pseudomonas aeruginosa strains. Also, the expression level of the alp virulence gene before and after treatment with cold plasma was compared with the Housekeeping gene gyrA. Materials and Methods: P. aeruginosa isolates recovered from hospitalized burn patients at Shahid Motahari Burns Hospital, Tehran, Iran. The Kirby Bauer disk diffusion method was used to determine the antimicrobial susceptibility test. Then, the antibacterial effect of atmospheric non-thermal plasma was evaluated on P. aeruginosa in as in vitro and in vivo studies at different times on Muller Hinton agar and in mouse model (treated by plasma every day/ 90 sec). The histopathological study was evaluated by Hematoxylin-Eosin staining. Data were analyzed using SPSS software by the Chi-square test and Pvalues less than 0.05 considered as statistically significant. Results: Results indicated that non-thermal atmospheric plasma inhibited the growth of P. aeruginosa. The non-thermal helium plasma accelerates wound healing for 6 days. Results showed that cold plasma decreased virulence gene expression alp after treatment. Therefore, cold plasma can be suggested as a complementary therapeutic protocol to reduce bacterial infection and accelerate wound healing and reduce the expression of virulence genes of pathogens. Conclusion: Cold plasma showed pathogen inhibitory properties of P. aeruginosa and virulence alkaline protease and wound healing properties in animal models, so this inexpensive and suitable method can be presented to the medical community to disinfect burn wounds and improve wound healing.